Application of three hygrometers under different skin conditions in dogs: dry, moist and haired skin. Issue 6 (3rd September 2017) - Momota, Yutaka; Shimada, Kenichiro; Minorikawa, Naoyuki; Gin, Azusa; Matsubara, Takako; Nakamura, Yuka; Katayama, Masaaki; Sako, Toshinori
Abstract : Background: Hydration is one parameter of skin barrier function. The Skicon‐200EX ® and Corneometer CM825 ® are hygrometers used to measure skin hydration in humans based on different measurement methods. The ASA‐MX3 ® is a hygrometer used to obtain measurements at haired skin sites in humans. Hypothesis/Objectives: To validate three hygrometers to measure skin dryness in dogs. Animals: Six clinically normal research dogs. Methods: In vivo evaluation of three hygrometers for three different skin types was performed. Measurement of hydration was performed at five different regional sites. Dry and moist skin were induced by treatment with a sorbent and petrolatum, respectively, and measurements were collected for 120 min. Skin sites with three different hair lengths were evaluated to determine whether hair would interfere with hydration measurements. Results: All three hygrometers obtained measurements at the nonhaired skin sites, except the ASA‐MX3 ® hygrometer at the ear site. At the dry skin sites the Skicon‐200EX ® hygrometer detected a significant decrease of water content for longer than the other devices. At the moist skin sites the Corneometer CM825 ® and ASA‐MX3 ® hygrometers showed a significant increase in water content. The ASA‐MX3 ® hygrometer was the only device that could obtain measurements at sites with hair. Conclusions and clinical importance: The Skicon‐200EX ® hygrometer was the most sensitive for detecting skin dryness, whereas the Corneometer CM825 ® and ASA‐MX3 ® hygrometers detected an emollient effect. Only the ASA‐MX3 ® could provide measurements at the haired sites. This study may assist in the selection of a hygrometer based on the purpose of use. Abstract : Background – Hydration is one parameter of skin barrier function. The Skicon‐200EX ® and Corneometer CM825 ® are hygrometers used to measure skin hydration in humans based on different measurement methods. The ASA‐MX3 ® is a hygrometer used to obtain measurements at haired skin sites in humans.Hypothesis/Objectives – To validate three hygrometers to measure skin dryness in dogs.Conclusions and clinical importance – The Skicon‐200EX ® hygrometer was the most sensitive for detecting skin dryness, whereas the Corneometer CM825 ® and ASA‐MX3 ® hygrometers detected an emollient effect. Only the ASA‐MX3 ® could provide measurements at the haired sites. This study may assist in the selection of a hygrometer based on the purpose of use.